The Implementation of Extensive Reading Using Line Webtoon to Enhance Students’ Reading Comprehension in Narrative Story - Asmara, Rizki Amalia (RETAIN, 2021)
Reading comprehension is one of the essential things in learning English at schools. In practice, reading is not easy for students to understand because of the complexity of the text and the lack of interest in the reading text. The purposes of this study are the implementation of extensive reading through LINE Webtoon to enhance students' reading comprehension and how students respond to its implementation. The descriptive-qualitative approach was carried out by observing the process of teaching and learning English activities carried out by the English teacher in an online class attended by 36 high school students and interviews with seven selected students in the class. The observation activity aims to observe the implementation of extensive reading using LINE Webtoon to enhance reading comprehension in a narrative story. In contrast, the interview activity aims to describe students' responses to the implementation. The data were obtained by using three instruments: (1) observation using check-list and field note in worksheets during two meetings; (2) questionnaire to select the students to be interviewed and; (3) interview. The results showed that the implementation of extensive reading using LINE Webtoon could enhance students' understanding of a narrative story. Students agreed that reading text with pictures makes it easier for them to understand the story’s context, even when they encounter unfamiliar words. Future researchers can develop further studies for other types of reading text as well as for listening, writing, and speaking skills.